2013
DOI: 10.1016/j.juro.2013.02.3229
|View full text |Cite
|
Sign up to set email alerts
|

Steatorrhea and Hyperoxaluria Occur after Gastric Bypass Surgery in Obese Rats Regardless of Dietary Fat or Oxalate

Abstract: Purpose To determine the effect of dietary fat and oxalate on fecal fat excretion and urine parameters in a rat model of Roux-en-Y gastric bypass (RYGB) surgery. Materials and Methods Diet-induced obese Sprague Dawley rats underwent sham (Control, n=16) or RYGB (n=19) surgery. Once recovered, animals were fed ad lib normal calcium, high fat (40%) diet with (Ox) or without (No Ox) 1.5% potassium oxalate for 5 weeks, then normal (10%) fat diet for 2 weeks. Stool and urine were collected after each period. Feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…In rats operated in our own laboratory, temporary malabsorption was also occasionally observed under conditions of high-fat feeding (e.g., 60% fat by calories), but the contribution to body weight loss seemed to be minor. A recent study by Canales et al (21) also indicated that fat malabsorption may be a direct consequence of RYGB surgery (21). In that study, it was, however, surprising that the relative fat absorption appeared to be higher when the rats were fed a 40% fat diet compared with a 10% fat diet; given that a limited capacity to absorb dietary fat in RYGB rats may have led to a ceiling effect for absolute fat transport capacity, we would have expected rather the opposite when fat absorption was expressed as percent absorption.…”
Section: Digestibility and Nutrient Absorption After Rygbmentioning
confidence: 93%
See 1 more Smart Citation
“…In rats operated in our own laboratory, temporary malabsorption was also occasionally observed under conditions of high-fat feeding (e.g., 60% fat by calories), but the contribution to body weight loss seemed to be minor. A recent study by Canales et al (21) also indicated that fat malabsorption may be a direct consequence of RYGB surgery (21). In that study, it was, however, surprising that the relative fat absorption appeared to be higher when the rats were fed a 40% fat diet compared with a 10% fat diet; given that a limited capacity to absorb dietary fat in RYGB rats may have led to a ceiling effect for absolute fat transport capacity, we would have expected rather the opposite when fat absorption was expressed as percent absorption.…”
Section: Digestibility and Nutrient Absorption After Rygbmentioning
confidence: 93%
“…Under conditions of high-fat feeding, macronutrient maldigestion and malabsorption may, at least in part, contribute to the negative energy balance of RYGB compared with shamoperated rats (21,143); in other words, caloric malabsorption may contribute to the RYGB-induced body weight loss if animals are maintained on a high-fat diet (21, 132, 143). In rats operated in our own laboratory, temporary malabsorption was also occasionally observed under conditions of high-fat feeding (e.g., 60% fat by calories), but the contribution to body weight loss seemed to be minor.…”
Section: Digestibility and Nutrient Absorption After Rygbmentioning
confidence: 99%
“…This study examined stool and urine for respective fecal fat content and [20] Free drinking of water with powdered 3% glycolic acid Hyperoxaluria Hypocitraturia CaOx crystal deposits Ethylene Glycol (EG) [16,21e29] 0 This study also found that all RYGB rats had a 250% increase in water consumption and a 2-fold increase in urine volume excretion, regardless of dietary oxalate or fat content. While postulated to be due to altered thirst mechanisms [46], it highlights a major difference compared to results from previous human studies that have shown significant decreases in urine volume post-RYGB [44,47,48]. Future studies are needed to further elucidate the impact of RYGB and urinary volume production.…”
Section: Gastric Bypass Surgerymentioning
confidence: 73%
“…Canales et al investigated the mechanism by which post-RYGB hyperoxaluria takes place by utilizing a diet induced obesity (DIO) model in male Sprague-Dawley rats followed by randomized intervention to either sham surgery (controls) or RYGB [46]. This study examined stool and urine for respective fecal fat content and [20] Free drinking of water with powdered 3% glycolic acid Hyperoxaluria Hypocitraturia CaOx crystal deposits Ethylene Glycol (EG) [16,21e29] 0 This study also found that all RYGB rats had a 250% increase in water consumption and a 2-fold increase in urine volume excretion, regardless of dietary oxalate or fat content.…”
Section: Gastric Bypass Surgerymentioning
confidence: 99%
“…Several groups have found experimental RYGB surgery to be associated with a development of a metabolic acidosis in rodents. 38,39 Likewise, the literature reports that citrate salts, such as potassium citrate, and alkali are able to play a role correcting hypocitraturia and metabolic acidosis. 15,28,32,40 Randomized controlled trials have demonstrated that potassium citrate is FIG.…”
Section: Citratementioning
confidence: 99%